2020
DOI: 10.14814/phy2.14555
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin analogs (B2BrBC and C66) supplementation attenuates airway hyperreactivity and promote airway relaxation in neonatal rats exposed to hyperoxia

Abstract: Background This study was undertaken to test the hypothesis that the newly synthesized curcuminoids B2BrBC and C66 supplementation will overcome hyperoxia‐induced tracheal hyperreactivity and impairment of relaxation of tracheal smooth muscle (TSM). Materials and methods Rat pups (P5) were exposed to hyperoxia (>95% O2) or normoxia for 7 days. At P12, tracheal cylinders were used to study in vitro contractile responses induced by methacholine (10−8–10−4M) or relaxation induced by electrical field stimulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In this direction, Wei et al [47] examined the protective capacity of THC after TBI and found a reduction of oxidative stress caused by brain contusion, reduction of cerebral edema, and reduced death of brain neurons. Different authors observed a curcuminoide-induced reduction in superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities as well as a decrease in MDA levels as markers of oxidative stress after TBI, cardiac damage, and bronchopulmonary dysplasia [48][49][50][51][52][53][54]. In addition, Wei et al [47] found an increase in the expression of pro-apoptotic factors in comparison to the expression of anti-apoptotic factors, resulting in Bax-dependent pore formation and increased cell permeability, followed by activation of caspase-3 and degradation of DNA and some critical proteins, ultimately resulting in cell death [19].…”
Section: Thc-related Induction Of Mitochondrial Apoptotic Route Autop...mentioning
confidence: 99%
“…In this direction, Wei et al [47] examined the protective capacity of THC after TBI and found a reduction of oxidative stress caused by brain contusion, reduction of cerebral edema, and reduced death of brain neurons. Different authors observed a curcuminoide-induced reduction in superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities as well as a decrease in MDA levels as markers of oxidative stress after TBI, cardiac damage, and bronchopulmonary dysplasia [48][49][50][51][52][53][54]. In addition, Wei et al [47] found an increase in the expression of pro-apoptotic factors in comparison to the expression of anti-apoptotic factors, resulting in Bax-dependent pore formation and increased cell permeability, followed by activation of caspase-3 and degradation of DNA and some critical proteins, ultimately resulting in cell death [19].…”
Section: Thc-related Induction Of Mitochondrial Apoptotic Route Autop...mentioning
confidence: 99%
“…Lung inflammation considered to be a risk factor for development of BPD and also contributes to increased, airway hyperresponsiveness in rats. 7,[9][10][11] Although there are many known pathophysiological mechanisms that lead to airway hyperreactivity, treatments for airway hyperreactivity among preterm survivors are surprisingly ineffective. Therefore, a therapy that could prevent neonatal hyperoxia-induced airway hyperreactivity and lung injury is imperative.…”
Section: Impact Statementmentioning
confidence: 99%
“…For example, the plant polyphenolic compound curcumin activates Nrf2 indirectly (Park et al 2021 ). Both curcumin (Sakurai et al 2013 ) and its synthetic analogues (Stamenkovska et al 2020 ) reduce lung damage due to hyperoxia in neonatal rats. Similar results have been obtained with resveratrol (Yang et al 2022 ).…”
Section: Therapeutic Approaches To Ameliorating Hyperoxia Injurymentioning
confidence: 99%